Application of Nanoprecipitation Technique to Develop Poloxamer-407 Facilitated Solid Lipid Nanoparticles for the Controlled Delivery of Tacrolimus - Muhammad Zaman; Asma Iqbal; Hafiz Shoaib Sarwar; Muhammad Hammad Butt; Muhammad Omer Iqbal; Naveed Nissar; Asma Mumtaz; Hafiza Yusra Nazeer; Abdulrahman Alshammari; Muhammad Shahid Riaz (International Journal of Polymer Science)
Currently, the solid lipid nanoparticles (SLNs) are utilized as a novel approach for the controlled drug delivery system (CDDS). Tacrolimus (TCM), a lipophilic drug, can easily be encapsulated in the hydrophobic core of these SLNs using nanoprecipitation technique. The current aim was to develop the controlled release Poloxamer (PLX) facilitated TCM loaded SLNs (PLX/TCM-SLNs), followed by their physicochemical evaluations, including chemical compatibility, particle size, surface charge, surface morphology, nature of SLNs, loading efficiency (LE), entrapment efficiency (EE), in vitro drug release studies, release kinetic modeling, and statistical evaluation. Here we also evaluate physicochemical properties of TCM and investigate solubility profile for improvement and dissolution rate of PLX/TCM-SLNs. PLX was used in the process as a polymer due to its low toxicity and weak immunogenic properties. The prepared formulation was characterized by scanning electron microscopy (SEM) images, and Fourier transform infrared spectroscopy (FTIR) has confirmed the compatibility of the selected ingredients, whereas particle size analysis showed that prepared PLX/TCM-SLNs were of nanosized (120.6±9 nm) having zeta potential of −21.3 Mv. On the other hand, SEM had revealed the smooth and uniform surface of the particle, while X-ray diffraction (XRD) confirmed the uniform surface as crystalline structure of TCM in PLX/TCM-SLNs masked. A satisfactory level of EE (94.5±2.74%) has also been noticed. Furthermore, in vitro drug release studies have explored the controlled release of drug during 8 hours, following zero order release kinetics and diffusion type of release mechanism. Outcomes of the studies have advocated the successful preparation of SLNs, as controlled release PLX/TCM-SLNs have been prepared efficiently.